Geothermobarometry of basaltic glasses from the Tamu Massif, Shatsky Rise oceanic plateau. (1st October 2013) - Husen, Anika; Almeev, Renat R.; Holtz, François; Koepke, Jürgen; Sano, Takashi; Mengel, Kurt
<x xml:space="preserve">Abstract</x> [1] We present the results of a petrological study of core samples from Tamu Massif (Site U1347), recovered during the Shatsky Rise Integrated Ocean Drilling Program (IODP) Expedition 324. The basaltic glasses from Site U1347 are evolved tholeiitic basalts containing 5.2–6.8 wt% MgO, and are principally located within the compositional field of mid‐ocean ridge basalts (MORBs) but they have systematically higher FeO, lower Al2O3, SiO2, and Na2O concentrations, and the CaO/Al2O3 ratios are among the highest known for MORBs. In this sense, glasses from Site U1347 more closely resemble basaltic magmas from the Ontong Java Plateau (OJP), although they still have lower SiO2 concentrations. In contrast to MORB and similar to OJP, our fractionation corrected values of Na2O and CaO/Al2O3 indicate more than 20% of partial melting of the mantle during the generation of the parental magmas of Tamu Massif. The water contents in the glasses, determined by midinfrared Fourier transform infrared (FTIR) spectroscopy, are MORB‐like, and vary between 0.18 and 0.6 wt% H2O. The calculated pressure (P)‐temperature (T) conditions at which the natural glasses represent cotectic olivine‐plagioclase‐clinopyroxene compositions range from 0.1 to 240 MPa and 1100 to 1150°C reflecting magma storage at shallow depth. The variation of the glass compositions and the modeled P‐T conditions in correlation with the relative ages indicate that there were at least two different magmatic cycles characterized by variations in eruptive styles (massive flows or pillow lavas), chemical compositions, volatile contents, and preeruptive P‐T conditions. Each magmatic cycle represents the progressive differentiation in course of polybaric crystallization after the injection of a more primitive magma batch. Magma crystallization and eruption episodes are followed by magmatic inactivity reflected in the core sequence by a sedimentary layer. Our data for Tamu Massif demonstrate that, similar to Ontong Java ocean Plateau, the crystallization beneath Shatsky Rise occurs at different crustal levels.